Analysis of terpenoids and their gene regulatory networks on the basis of the transcriptome and metabolome of Opisthopappus longilobus - Liu, Hua; Chai, Yuhong; Chen, Haixia; Chen, Wendan; Li, Yushu; Liu, Wenchao; Guo, Shuang; Sun, Lei; Zhou, Xiumei; Huang, Conglin; Tang, Xiaowei; Luo, Chang; et al. (Frontiers in Plant Science, 2022)
Opisthopappus longilobus, which is a unique wild plant resource in China, produces branches, leaves, and flowers with distinct aromas. However, there have been relatively few molecular studies on its floral aroma, which has hindered the research on this plant species at the molecular level and the breeding of novel varieties. In this study, transcriptome and metabolome analyses were performed using O. longilobus leaves at the flowering stage and the inflorescences at different developmental stages (bud, exposure, initial opening, and blooming stages). Using high-quality reads and assembly software, 95,114 unigene sequences were assembled. A total of 45,674 unigenes were annotated according to the Nr, Swiss-Prot, KOG, and KEGG databases. Additionally, a GC-MS system and a self-built database were used to detect 1,371 metabolites in the leaves and inflorescences. Terpene metabolites were the most common compounds (308 in total). We analyzed the gene network regulating terpenoid accumulation in O. longilobus, which led to the identification of 56 candidate genes related to terpenoid synthesis. We observed that OlMVK1, OlPMK2, OlTPS1, and OlTPS3 were specifically expressed in the inflorescences, which may contribute to the specific accumulation of 11 kinds of terpenoids in the inflorescences. In this study, we revealed the changes in the terpenoid metabolites in the leaves and inflorescences as well as the corresponding gene regulatory network. The generated data may be useful for future research on O. longilobus genetic resources and the molecular mechanism regulating aroma formation in this plant species. The findings of this study may also accelerate the breeding of new O. longilobus varieties with enhanced aromatic traits.